Immunity to poliovirus serotypes In Children population of selected communities in South-West, Nigeria (2015)
"Poliovirus outbreaks are still reported in Nigeria despite renewed efforts to improve vaccine coverage, thus suggesting the existence of susceptible hosts. Also, there is anecdotal evidence of variation in vaccine coverage by region and specifically between urban and rural communities. Consequently, this study assessed neutralizing antibodies to poliovirus serotypes among children in selected urban and rural communities in south western Nigeria. Two hundred and forty-four {(M=119, F=125); Urban: 142 (M=63, F=79); Rural: 102 (M=56, F=46)} children of consenting parent/guardian aged one week to 15 years were enrolled for the study. About 2-3ml of blood was collected from each child by venepuncture into a labelled sterile container free of anticoagulants. Subsequently, questionnaire was administered to the parent/guardian of each child to retrieve relevant information. Recovered sera were analysed for detectable neutralizing antibodies to poliovirus serotypes by the standard method of constant virus, varying serum dilutions. Overall, 64.3% (n=157) of the children had detectable neutralizing antibodies to the three poliovirus serotypes. Also, 84.8% (n=207), 91.0% (n=222) and 75.0% (n=183) of the children had detectable antibodies to poliovirus serotypes 1, 2 and 3 respectively. Eighty seven (35.7%) of the children had no detectable neutralizing antibody to at least one of the three poliovirus serotypes, while 9 (3.7%) children had no detectable neutralizing antibody to the three poliovirus serotypes. Geometric mean titre (GMT) of neutralizing antibodies to the three poliovirus serotypes varied significantly (p=0.0005). Disparity in immunity to poliovirus infection and existence of children with low or zero neutralizing antibody levels were confirmed.